PENGARUH METODE LATIHAN INTERVAL 1:1 DAN METODE LATIHAN INTERVAL 1:2 TERHADAP KECEPATAN RENANG 50 METER GAYA CRAWL - Prihanti, Sheni via (Universitas Negeri Semarang, 2017)
The interval is the method training exercises, where athletes alternately put up between the interval working with the interval break. This report aims to understand 1) influence method of the interval 1:1 to the speed pool 50 meters style crawl. 2) influence method of the interval 1:2 to the speed pool 50 meters style crawl. 3) the difference between a method of exercise interval 1:1 and methods exercise interval 1:2 to the speed pool 50 meters style crawl. The results of the study showed: 1)  there is no difference the influence of a method of exercise intervals 1:1 to the speed swimming 50 meters style crawl obtained t count (1.081) < t table (4.303),  2) there is a difference the influence of a method of exercise intervals 1:2 to the speed swimming 50 meters style crawl obtained t count (9.690) >( 4.303 ), 3) there is no difference between a method of exercise intervals 1:1 and methods exercise intervals 1:2 tehadap speed swimming 50 meters style crawl, obtained t count (-0.686) < t table (4.303).